The Influence of Nutritional Labels and Health Awareness on Frozen Food Purchase Decisions - Ayu Pujiarti; Lalu Muhammad Furkan (LP2M IAIN Palopo, 2026)
The increase in frozen food consumption along with modern lifestyles emphasizes the need to understand the factors influencing purchasing decisions. This study aims to analyze the influence of nutritional labels and health awareness on purchasing decisions for frozen food products among the people of Mataram City. Using a quantitative associative-causal approach, data were collected through an online questionnaire from 100 purposive sampling respondents with multiple linear regression analysis in SPSS 27. The results showed that nutritional labels (t=2.316, p=0.023) and health awareness (t=7.664, p=0.000) had a significant effect both partially and simultaneously (F=49.856, p=0.000), explaining 50.7% of the variation (R²=0.507). The conclusion states that clear nutritional information and high health awareness encourage selective purchasing among young female students, so manufacturers are advised to improve label quality and the government to promote nutritional literacy for healthier consumption.